A retrospective analysis with bibliometric of energy security in 2000-2017 - Wei Zhou; Aiqing Kou; Jin Chen; Bingqing Ding (Energy Reports, 2018)
In recent years, some countries are facing the problem of energy security. Energy security is an important factor affecting the national economy and environment. There are many investigations about energy security, but few of them are bibliometric analysis, including co-citation analysis, hot topics, burst detection, and emerging trends. Therefore, this paper adopts a bibliometric method to address the above issues and provide a general picture of the research field. By downloading 2845 articles from Web of Science and analyzing the results given by CiteSpace, the main conclusions of the most productive countries, institutions, sources, authors, and interesting research directions in the energy security researches are visually demonstrated. For instance, Energy Policy, Renewable Sustainable Energy Reviews, and Applied Energy are the major sources for energy security researches. The emerging trends in energy security researches are energy security, the exploring proposition, the integrated assessment. This paper provides an overall analysis of energy security researches and gives some inspirations for the researchers in this area to do further investigations.
Keywords: 330; Energy security; Bibliometric method; CiteSpace; Diversity; National economy